Psychology of democracy of the people, by the people, for the people - Weinberg, Ashley 1965- (Cambridge University Press, 2022)
Democracy was forged in the furnaces of oppression, whether combatting tyranny or affirming the rights of the individual. As democracy is under threat in many parts of the world, there has never been a more urgent need to understand political thoughts and behaviours. This lucid and accessible book brings together a global group of scholars from psychology, political science, communication, sociology, education and psychiatry. The book's structure, based on Abraham Lincoln's well-known phrase 'Of, by and for' the people, scrutinises the psychological factors experienced by politicians as representatives 'of' the electorate, the political institutions and systems devised 'by' those we elect, and the societies that influence the context 'for' us as citizens. From trust to risk, from political values to moral and religious priorities, from the personality and language of leaders to fake news and anti-democratic forces, this book provides vital new insights for researchers, politicians and citizens alike